(untitled) (CIPEEX, 2025)
This article analyzes the rise of China as a global economic power, focusing on the perception of the "Made in China" and "Made in PRC" brands and their impact on consumer influence. Based on the theories of soft power and country branding, the study begins with an analysis of the structural foundations of today’s technology industry. It discusses the deterioration of the "Made in China" brand image due to its association with low quality, counterfeiting, and dumping practices. The counterpoint of private initiative in changing labels is recognized, as the domestic economy reflects China’s transition to a territory synonymous with innovation and quality. It also addresses state management efforts to control the commercial illegalities that are increasingly gaining representation on the global stage. The article highlights the importance of country-brand management and proposes exploring "China’s Commercial Identity" as a promising field for future studies, aiming to understand its evolution in the face of global economic dynamics.